Variance and clustering - Yatracos, Yannis G. (My University, 1998)
A measure of dissimilarity of real observations is introduced that is used to identify clusters and is based on "gaps", and also on averages of selected subgroups of the observations. This measure is surprisingly associated with the sample variance in a way that leads to a new identity and interpretation of the notion of variance.
Keywords: Analysis of variance